REDEFINING URBAN-RURAL BOUNDARIES FROM THE DIGITAL DISPARITY PERSPECTIVE - Mahmoud, Zakaria Alcheikh; Nordin, Nikmatul Adha; Md Dali, Melasutra; SH, Yong Adilah; Rawashdeh, Taiseer Mustafa; Mahmoud, Sara Alcheikh (PLANNING MALAYSIA, 2022)
There is no international consensus on a comprehensive criterion to classify human settlements into urban and rural settlements. Different national criteria are used for delineating the borders between the two types of settlements. The main components of the criteria are population size, population density, population economic activity, administrative and legal and services and facilities. Whether all these criteria have been used or some of them, an outright socio-cultural and economic distinction between the two categories of settlements have developed over years around the world. The widely used virtual space during the pandemic provided people with access to facilities and services and enabled them to work for places that usually require their physical presence. The literature has not yet covered this point. Therefore, this paper aims at revisiting the classification of urban and rural areas in the COVID-19 aftermath. Through desk work and employing qualitative and quantitative research approaches, secondary data was collected from published relevant journals, reports, books, and websites. Content and comparative analysis for analysing qualitative data and content and quantitative comparative analysis and tabulation were used to carry out the research. This paper suggested that the world is in a transitional period towards full urban status. During this period, accessibility to virtual space can be used as a comprehensive criterion for calcifying human settlements into urban and rural.